Small, stable and biocompatible gold nanoparticles capped with a β-cyclodextrin polymer. Issue 119 (18th November 2015) - Martin-Trasanco, Rudy; Cao, Roberto; Esparza-Ponce, Hilda E.; García-Pupo, Laura; Montero-Cabrera, Maria E.
Abstract : Gold nanoparticles capped with a β-cyclodextrin epichlorohydrin polymer resulted to be smaller than 5 nm, stable in physiological fluid and biocompatible, features that denote their capability as scaffold for future applications in nanomedicine. Abstract : The preparation of colloidal gold nanoparticles (AuNPs) capped with β-cyclodextrin-epichlorohydrin polymer (AuNP@βCDP) was achieved by the reduction of gold(iii ) with trisodium citrate in the presence of the polymer (βCDP), both in different proportions. The gold nanoparticles showed a mean diameter of 4.8 nm with a narrow size distribution (±0.8 nm). The βCD polymer conferred a high water solubility and stability to the nanoparticles, even at high concentrations. The use of βCDP as a capping agent allowed the redispersion of precipitated nanoparticles without altering their size and optical properties. The stability of the AuNP@βCDP was evaluated in human blood serum. The nanoparticles retained 100% of their stability during 14 days of exposure to physiological fluid. An absence of cytotoxicity in SHSY5Y culture cells was observed at concentrations less than 0.1 mg mL −1 .